2021
DOI: 10.3390/pharmaceutics13111823
|View full text |Cite
|
Sign up to set email alerts
|

Major Phytocannabinoids and Their Related Compounds: Should We Only Search for Drugs That Act on Cannabinoid Receptors?

Abstract: The most important discoveries in pharmacology, such as certain classes of analgesics or chemotherapeutics, started from natural extracts which have been found to have effects in traditional medicine. Cannabis, traditionally used in Asia for the treatment of pain, nausea, spasms, sleep, depression, and low appetite, is still a good candidate for the development of new compounds. If initially all attention was directed to the endocannabinoid system, recent studies suggest that many of the clinically proven effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 198 publications
(310 reference statements)
0
41
0
1
Order By: Relevance
“…Dermal fibroblasts treated with CBD activate PPARγ and decrease nuclear factor kappa B (NF-kB) levels [53]. In silico studies identified CBG as a PPARα/γ dual agonist [54], and a quinone derivative of CBG has also been suggested to modulate PPARγ [55]. Future research could examine if CBG activates PPARγ and PPARα in dermal cells given their key function in epidermal biology.…”
Section: Discussionmentioning
confidence: 99%
“…Dermal fibroblasts treated with CBD activate PPARγ and decrease nuclear factor kappa B (NF-kB) levels [53]. In silico studies identified CBG as a PPARα/γ dual agonist [54], and a quinone derivative of CBG has also been suggested to modulate PPARγ [55]. Future research could examine if CBG activates PPARγ and PPARα in dermal cells given their key function in epidermal biology.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that cannabinoids effectively alleviate neuropathic, in ammatory and cancer-related pain [9]. CBD and THCV are major phytocannabinoids that have received signi cant attention as therapeutic agents in various applications (e.g., anxiety, aging, obesity, cancer, pain, and other CNS diseases) [10]. Unlike THC, which is psychoactive and acts as an agonist at both the CB1 and CB2 receptors, THCV is a non-psychoactive, neutral CB1 antagonist/reverse agonist that can behave as a partial agonist or antagonist at the CB2 receptors depending on the dose.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies on its therapeutic properties indicate that CBD is a negative allosteric modulator of cannabinoid (CB) receptors [ 26 ] and may modulate endogenous endocannabinoid (eCB) levels by indirect mechanisms involving the nuclear receptor peroxisome proliferator-activated receptor-α (PPAR-α) and PPAR-α-independent pathways, such as Transient Receptor Potential Vanilloid 1 (TRPV1) and G55 protein-coupled receptor (GPR55) [ 27 ]. Consistent with this, recent research highlighted the importance of widening the investigation to cannabinoid-related compounds whose actions depend on the interaction with non-CB receptors [ 28 ]. Overall, this review demonstrated that PEA, a naturally occurring N-acylethanolamine whose biological effects are related to indirect activation of CB1 receptors as well as PPAR-α and TRPV1 modulation [ 8 , 19 ], may be involved in seizures and epilepsy.…”
Section: Discussionmentioning
confidence: 93%